A Socratic History: Theology in Xenophon's Rewriting of Herodotus' Croesus Logos. (13th December 2016) - Ellis, Anthony
Abstract: This article examines Xenophon's rewriting of Herodotus' Croesus logos (Hdt. 1.6–91) in the Cyropaedia ( Cyr. 7.2), focusing on the very different role of the divine in the two narratives. Through a comparison with Xenophon's Memorabilia and several Platonic dialogues, I argue that Xenophon's retelling attempts to bring Herodotus' Croesus logos in line with his own 'Socratic' theology and his pedagogical goals, and in doing so performatively rejects Herodotus' vision of the role of the gods in historical causation. The Cyropaedia is, I argue, the first extant text in the Greek historiographical tradition which attempts to present divine justice and philanthropy as the central forces in the historical process, and the first in a long series of critical engagements with Herodotus' theology.